The Determinants of Loyalty to Ecotourism against the Background of Consumer Satisfaction - HOANG, Sinh Duc; NGO, Ngoc Thuyen; NGUYEN, Diep T.N.; NGUYEN, Thi Thu Huong; TUČKOVÁ, Zuzana (Journal of Environmental Management and Tourism, 2022)
The desire to gain knowledge about the cultural identity and nature of unexplored places has been inherent in humans since time immemorial. However, the emergence of motivation to care, preserve and increase the cultural, historical, natural and recreational values of destinations indicates a higher level of consciousness and responsibility of tourists. The commitment of tourists to this kind of travel is caused not only by marketing prerequisites, but also by socio-psychological factors different: responsibility, psychological ownership. Due to international competition, the relevance of improving the tourist image is increasing, for which it is necessary to develop the concept of socially and environmentally responsible tourism, develop useful behavioral attitudes in society, which increases the role of transfer of cultural and natural knowledge, consolidation of tourists and local residents in improving the tourist image. The study considers the construct of loyalty to a particular destination. The aim of the study is to deepen the analysis of socio-psychological factors of loyalty to ecotourism and develop a methodology for their study. On the basis of correlational, empirical and sociological methods the direct correlation between loyalty and responsibility, satisfaction, positive experience, psychological property and image of the destination was substantiated. It is proved that research activity, intellectual preparation, motivation, respect for nature, cultural involvement and involvement of local residents have a positive effect on the level of responsibility. Cultural involvement and protection of nature, psychological attachment and social interaction increase the sense of psychological ownership, in contrast to the massiveness factor of the place, which decreases it.